The Correlation between Lecturer Personality and Students’ Reading Achievement in Reading Comprehension - Yukir, Muh. (Majesty Journal, 2023)
This study aims to investigate the correlation between lecturer personality and students’ reading achievement in reading comprehension. It also examines the influence of lecturer personality on students’ achievement in a reading course. The study employed a descriptive quantitative design with a correlational approach. The population consisted of English Education students at Universitas Muhammadiyah Enrekang in the 2021/2022 academic year. The sample comprised 14 first-semester students selected through purposive sampling because they were taking an intensive reading course. Data were collected using a questionnaire on lecturer personality and students’ reading achievement scores obtained from the reading lecturer. The data were analyzed using SPSS version 25 to determine the correlation between the variables. The findings showed that the correlation coefficient between lecturer personality and students’ reading achievement was 0.441, indicating a moderate correlation. In addition, the Chi-square analysis showed that the obtained value was higher than the table value (60.7225 ≥ 55.76), indicating a significant influence of lecturer personality on students’ reading achievement. These findings suggest that lecturer personality contributes to students’ reading achievement by supporting motivation, classroom engagement, and learning comfort. Therefore, lecturers are expected to demonstrate positive personal characteristics, such as fairness, patience, friendliness, clarity, self-control, and appreciation of students’ opinions, to create a more supportive reading classroom environment.